Array tracking of the volcanic tremor source at Deception Island Antarctica - Almendros, J.; Ibanez, J.; Alguacil, G.; Del Pezzo, E.; Ortiz, R. (American Geophysical Union, 1997)
We have found experimental evidence which shows that the volcanic tremor recorded at Deception Island (South Shetland Islands, Antarctica) is a superposition in time of overlapping hybrid events. Published 3069-3072 3.1. Fisica dei terremoti JCR Journal reserved